Qualitative assessment of water of the Al-Khazer river between Mosul and Erbil city - Eman Al-Sarraj (College of Education for Pure Sciences, 2020)
This paper discusses the results of a study carried out from the period of December 2017 to April 2018, on assessing water quality of Al-Khazer river between Mosul and Erbil City. Al-Khazer river is considered as one of the tributaries of Al-Zab river that flow into the Tigris river. Three locations were chosen in order to evaluate its suitability, as resources of raw water, for human, industrial and agricultural uses. The spectral methods have been used to assign some of the physiochemical parameters, which include Water temperature, Turbidity, Electrical conductivity, pH, Dissolved oxygen, Total hardness, Chloride, Sulfate, Nitrate and Orthophosphate. Results showed that all  values were within permissible limits and the water of Al-Khazer river were hardened water and suitable for drinking, irrigation, swimming as well as different uses for agriculture and industry.